Studies On The Properties Of Conductive Particulate Fillers Filled Rubber Composites - Mat Junoh, Mohd Anuar (2008)

(untitled)
The use conductive fillers on properties of rubber composites were studied. Three types of conductive filler has been used in this study i.e. aluminium, zinc and carbon black. Natural rubber (NR) and Ethylene-Propylene-Diene terpolymer (EPDM) were chosen as a matrix. Compounding was carried out using two roll mill based on a semiefficient vulcanization (semi-EV) system. The investigation of rubber composites properties involves curing characteristics, mechanical and electrical properties, thermogravimetric analysis (TGA) , morphological study and swelling behavior. Penggunaan pengisi-pengisi konduktif ke atas sifat-sifat komposit getah telah dikaji. Tiga jenis pengisi konduktif telah digunakan dalam kajian ini iaitu aluminium, zink dan hitam karbon. Getah asli dan Ethylene-Propylene-Diene terpolymer (EPDM) telah dipilih sebagai matriks. Penyebatian telah dijalankan menggunakan penggiling bergulung dua berdasarkan sistem pemvulkanan separuh cekap (semi EV). Penyelidikan sifat-sifat bahan komposit getah melibatkan ciri-ciri pematangan, sifatsifat mekanikal dan elektrikal, analisis termogravimetri (TGA), kajian morfologi dan tingkah laku pembengkakan.